Integrated Proteotranscriptomics of Human Myometrium in Labor Landscape Reveals the Increased Molecular Associated With Inflammation Under Hypoxia Stress - Chen, Lina; Wang, Lele; Luo, Yihong; Huang, Qian; Ji, Kaiyuan; Bao, Junjie; Liu, Huishu (Frontiers in Immunology, 2021)
During labor, a variety of coordinated physiological and biochemical events cause the myometrium to transition from a quiescent to contractile state; the molecular mechanisms responsible for this transition, however, remain unclear. To better understand of this transition at a molecular level, the global transcriptome and proteome of human myometrial samples in labor and those not in labour were investigated through RNA sequencing (RNA-seq) and quantitative liquid chromatography-tandem mass spectrometry (LC-MS/MS) untargeted (DIA) and targeted (PRM) methods. Furthermore, an integrated proteotranscriptomic analysis was performed to explore biological processes and pathways alterations during labor; this analysis identified 1626 differentially expressed mRNAs (1101 up-regulated, 525 down-regulated) were identified and 135 differentially expressed proteins (97 up-regulated, 38 down-regulated) in myometrium between non-labor and in labor groups. The comprehensive results of these analyses show that the up-regulated mRNAs and proteins increased inflammation under hypoxia stress in myometria under labor, related proteins and cytokines were validated by PRM and Luminex assays. Our study confirmed the biological process of inflammation and hypoxia in laboring myometrium at the transcriptome and proteome levels, and provided recourse to discover new molecular and biological changes during labor.